(untitled) (Architecture Image Studies, 2026)
In many buildings atrium has been designed with various shapes and forms. The main purpose to design atrium is to get good quality of day light and also to make building more ventilated. Such attempts to optimizing the atrium size is very important because it not only improve the natural daylight inside the building but also reduce the heating and cooling load, hence reduces the electrical load in the building. The geometry of atrium is defined by the atrium well index (WI). This paper is focusing on the effect of daylight in atrium and adjoining areas, keeping the well index constant by varying the parameters like height, width and length ratio of atrium wells and also to examine effect on daylight in atrium and adjoining areas by different shapes of atrium like circular, square and rectangle having equal atrium shapes areas. The amount of average lux, spatial daylight autonomy and annual sunlight exposure is studied by software simulation. The average daylight factor is very important parameter to examine the light level. The 3D software model of various atrium forms is created and its performance is studied by software simulation. Day lighting analysis is done using Climate Studio tool with Rhinoceros 3D 7.0. Built on Energy Plus and a novel radiance-based path tracing technology.